Minisink Valley Reformed Dutch Church records - Vosburgh, Royden Woodward (Collections of the New York Genealogical and Biographical Society, 1913)
Minisink-Machackemeck church record, 1716-1803.--Minisink church record, 1805-1816.--Machackemeck church record, 1803-1827.--Walpack church record, 1741-1830.